Neoclassical concept of marketing information systems of the companies - Педько, Ірина Анатоліївна (Technology audit and production reserves, 2015)
The article shows that the new challenges facing enterprises necessitated concept modernization of marketing information systems. The neoclassical concept of marketing information system is proposed, its definition, purpose, objectives, principles on which the goal is achieved and tasks, solutions to problems faced by enterprises and structure of the system are given. It is shown that marketing information system of the concrete and the concrete product manufacturer – is the organizational and administrative mechanism for the aggregation, processing, analysis of valuable information needed to develop forecasts for the enterprise under uncertainty and risk marketing environment. It is proposed the scheme of neoclassical concept of marketing information systems of the enterprise which consists of the following four subsystems: monitoring; marketing research; risk assessment; forecasting.